Culturing the Unculturable: A DIY, high-throughput system for the culturing, isolation and characterisation of bacterial microbiomes - Chia, Aletheia Zhi Hui (2016)
Recent advances in genomic analysis have enabled an explosion in microbiomics, leading to new insights into the millions of bacteria we carry around and their impact on human health and disease. However current culture-independent methods (16s rRNA, metagenomics) are limited, and a true understanding of these bacterial ecosystems would require phenotypic studies; ie culturing. [3rd Award]